Microfluidic Chips for Formulation of Silica Nanoparticles and Enzyme Immobilization - Fiona Ling, Wang Ming; Abdulbari, Hayder A.; Chin, Sim Yee (Wiley, 2021)
The unique micromixing environment of microfluidic technology provides new opportunities to apply known nanoparticle formulation techniques for higher reaction rates and better product quality. Novel methods to formulate silica nanoparticles and immobilize Rhizomucor miehei lipase on these particles in a microflow environment are introduced. The quality of the formulated nanoparticles from the microfluidic reactor was compared with those produced in the traditional bench-scale method. The results demonstrate that the smaller silica nanoparticles were produced from the microfluidic reactor with higher dispersity compared to nanoparticles obtained from the bench-scale. Immobilization of lipase is found to be more effective using silica nanoparticles synthesized in microflow systems as the carriers.